PENGARUH PEMBELAJARAN INKUIRI TERHADAP AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK - ., Burhanuddin (Inspiratif Pendidikan, 2017)
In an effort to improve the quality of education, educational institutions is one place that can provide supplies to humans to free themselves from ignorance and backwardness. In an effort to improve the quality of educational resources, teachers are a component of human resources in the learning process. Therefore, every teacher in preparing the learning should really plan with the best that can give the competence of learners and pay attention to the needs of the learners, so that the learning can bring changes to the students themselves. Because the improvement of learning outcomes will have an impact on improving the quality of education for the development of Indonesian human resources. One effort that teachers need to do in improving learning outcomes is to increase the activities and interests of learners learn.